2022
DOI: 10.1029/2021jc017424
|View full text |Cite
|
Sign up to set email alerts
|

Summer Surface CO2 Dynamics on the Bering Sea and Eastern Chukchi Sea Shelves From 1989 to 2019

Abstract: By compiling boreal summer (June to October) CO2 measurements from 1989 to 2019 on the Bering and eastern Chukchi Sea shelves, we find that the study areas act as a CO2 sink except when impacted by river runoff and wind‐driven upwelling. The CO2 system in this area is seasonally dominated by the biological pump especially in the northern Bering Sea and near Hanna Shoal, while wind‐driven upwelling of CO2‐rich bottom water can cause episodic outgassing. Seasonal surface ΔfCO2 (oceanic fCO2 – air fCO2) is domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 104 publications
0
21
0
Order By: Relevance
“…To focus on the Chukchi shelf, data used for this study were limited from 66°N to 74°N to a maximum of 120 m to exclude deep waters from the Canada Basin. We adopted the water mass classification used by several previous studies (Table 2 ; Corlett and Pickart et al., 2017 ; Gong & Pickart, 2015 ; Pacini et al., 2019 ; Pickart et al., 2019 ; Wang et al., 2022 ). The coldest water is known as Newly‐Ventilated Winter Water (NVWW; T < −1.6°C), which is typically observed from spring to early‐summer over the entire shelf.…”
Section: Methodsmentioning
confidence: 99%
“…To focus on the Chukchi shelf, data used for this study were limited from 66°N to 74°N to a maximum of 120 m to exclude deep waters from the Canada Basin. We adopted the water mass classification used by several previous studies (Table 2 ; Corlett and Pickart et al., 2017 ; Gong & Pickart, 2015 ; Pacini et al., 2019 ; Pickart et al., 2019 ; Wang et al., 2022 ). The coldest water is known as Newly‐Ventilated Winter Water (NVWW; T < −1.6°C), which is typically observed from spring to early‐summer over the entire shelf.…”
Section: Methodsmentioning
confidence: 99%
“…The northern Gulf of Alaska (NGA) is a predominantly downwelling system (Royer and Emery, 1987) with seasonal exceptions. When the onshore surface Ekman transport relaxes in the summer, deep, nutrient-rich, cold water can inundate the continental shelf below the surface layer near the shore (Weingartner et al, 2005). The new intermediate water, also enriched in CO 2 , causes the saturation horizon for both aragonite and calcite minerals to shoal to within 100 and 250 m from the surface respectively (Feely et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. (2022) have examined summer surface‐water CO 2 dynamics in the Bering Sea and Chukchi Shelf using SOCAT fCO 2 and fCO 2 data collected by unmanned surface vehicles. Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2022) have examined summer surface-water CO 2 dynamics in the Bering Sea and Chukchi Shelf using SOCAT fCO 2 and fCO 2 data collected by unmanned surface vehicles. Wang et al (2022) have found that in early summer, high net primary productivity sustained by nutrients supplied via Bering Summer Water maintains a strong summer CO 2 sink, whereas in late summer, strong upwelling and vertical mixing induced by northerly winds results in CO 2 outgassing. In summary, recent studies have indicated that there are distinct differences of spatiotemporal variations of the CO 2 sink between shelf (Chukchi Shelf) and basin (Canada Basin) and that expansion of open sea due to sea ice loss does not necessarily lead to increases of CO 2 uptake.…”
mentioning
confidence: 99%
See 1 more Smart Citation